Adaptation of the Manchester-Minneapolis Quality of Life instrument for use in the UK population. Issue 10 (23rd May 2007) - Hutchings, H A; Upton, P; Cheung, W-Y; Maddocks, A; Eiser, C; Williams, J G; Russell, I T; Jackson, S; Jenney, M E M
Abstract : Introduction: The availability of health-related quality of life (HRQL) measures that are reliable, valid, brief and comprehensible and appropriate for use with UK children is limited. We report the validation of a HRQL measure suitable for UK use in healthy children, children with chronic disease conditions and socially disadvantaged children. Patients: A total of 1238 children took part in the study, including healthy children as controls (n = 824) and five exemplar groups: children diagnosed with asthma (n = 87), diabetes (n = 103) or inflammatory bowel disease (IBD; n = 69), children in remission from cancer (n = 68) and children in public care (n = 87). Methods: In phase I, the Manchester-Minneapolis Quality of Life instrument (MMQL) Child Form was translated into UK English. In phases II and III, the questionnaire was shortened and validated. Results: MMQL was anglicised and shortened to five components comprising 29 items. Good internal reliability was found with α reaching at least 0.69 for all subscales. Construct validity was established through moderate correlations with comparable PedsQL subscales (Pearson's r ranged from 0.38 to 0.58, p<0.01). Discriminant validity was also demonstrated in children with asthma and IBD, children in remission from cancer and children in public care, all of whom reported significantly lower HRQL than healthy children. Children with diabetes showed similar HRQL to their healthy peers. Good reproducibility and moderate responsiveness were demonstrated for the new measure. Conclusions: The anglicised and shortened MMQL was shown to be valid and reliable and could be a valuable new tool for the assessment of HRQL in children.